2013
DOI: 10.1128/jvi.00718-12
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity and Immunogenicity of RV144 Vaccine AIDSVAX Clade E Envelope Immunogen Is Enhanced by a gp120 N-Terminal Deletion

Abstract: An immune correlates analysis of the RV144 HIV-1 vaccine trial revealed that antibody responses to the gp120 V1/V2 region correlated inversely with infection risk. The RV144 protein immunogens (A244-rp120 and MN-rgp120) were modified by an N-terminal 11-amino-acid deletion (Δ11) and addition of a herpes simplex virus (HSV) gD protein-derived tag (gD). We investigated the effects of these modifications on gp120 expression, antigenicity, and immunogenicity by comparing unmodified A244 gp120 with both Δ11 deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 39 publications
4
107
0
Order By: Relevance
“…However, the differences seen here suggest substantial differences in epitope focusing of the IgG responses elicited by SIVmac239 and HIV-1 Env immunogens. Notably, NHPs immunized with A/E A244, the RV144 vaccine strain immunogen, developed a strong V2-specific response, consistent with the antigenic features of this immunogen (36), whereas binding to the MN gp120 vaccine strain in the same study was strongly dominated by the anti-V3 response. Our study results suggest that understanding how vaccine inserts and regimens induce differential dominant antibody specificities is important for vaccine immunogen design.…”
mentioning
confidence: 68%
“…However, the differences seen here suggest substantial differences in epitope focusing of the IgG responses elicited by SIVmac239 and HIV-1 Env immunogens. Notably, NHPs immunized with A/E A244, the RV144 vaccine strain immunogen, developed a strong V2-specific response, consistent with the antigenic features of this immunogen (36), whereas binding to the MN gp120 vaccine strain in the same study was strongly dominated by the anti-V3 response. Our study results suggest that understanding how vaccine inserts and regimens induce differential dominant antibody specificities is important for vaccine immunogen design.…”
mentioning
confidence: 68%
“…Genes for four HIV-1 T/F gp120s, including three subtype B proteins (B.040, B.65321, and B.6240) and one subtype C protein (C.1086) obtained from subjects acutely infected with HIV-1 by single-genome amplification, were described previously (27,28). All gp120 genes were codon optimized by converting amino acid sequences to nucleotide sequences by employing the codon usage of highly expressed human housekeeping genes (29) synthesized de novo for expression as gp120 with deletion of either 7 (C.1086⌬7gp120) or 11 (B.040⌬11gp120, B.65321⌬11gp120, and B.6240⌬11gp120) amino acid residues at the N terminus of the mature HIV-1 Env proteins (30,31). These genes were then cloned into a mammalian expression plasmid, pcDNA3.1/hygromycin (Invitrogen, Grand Island, NY).…”
Section: Cellsmentioning
confidence: 99%
“…It is widely believed that an effective antibody-based HIV-1 vaccine would need to elicit antibodies capable of recognizing diverse Env isolates, ideally including "broadly" neutralizing antibodies (NAbs) as well as nonneutralizing antibodies with antibody-dependent cellular cytotoxicity (ADCC) effector functions, which appeared to correlate with protection in the RV144 HIV-1 vaccine trial (9). Indeed, the hopeful results of the RV144 trial, which provided evidence that vaccine-induced protection against HIV-1 may be possible (10), suggested that monomeric gp120 is a relevant HIV-1 vaccine immunogen and highlighted the importance of understanding the structural features that distinguish gp120 proteins and influence gp120 reactivity with neutralizing and ADCCactive antibodies (11)(12)(13).…”
mentioning
confidence: 99%